Complete genome sequence of Arthrobacter sp. strain FB24. Issue 1 (July 2013) - Nakatsu, Cindy; Barabote, Ravi; Thompson, Sue; Bruce, David; Detter, Chris; Brettin, Thomas; Han, Cliff; Beasley, Federico; Chen, Weimin; Konopka, Allan; Xie, Gary
Abstract Arthrobacter sp. strain FB24 is a species in the genusArthrobacter Conn and Dimmick 1947, in the familyMicrococcaceae and classActinobacteria . A number ofArthrobacter genome sequences have been completed because of their important role in soil, especially bioremediation. This isolate is of special interest because it is tolerant to multiple metals and it is extremely resistant to elevated concentrations of chromate. The genome consists of a 4, 698, 945 bp circular chromosome and three plasmids (96, 488, 115, 507, and 159, 536 bp, a total of 5, 070, 478 bp), coding 4, 536 proteins of which 1, 257 are without known function. This genome was sequenced as part of the DOE Joint Genome Institute Program.